Koyaanisqatsi [videorecording (DVD)] - Coppola, Francis Ford, 1939-; Reggio, Godfrey; Glass, Philip; Ginsberg, Allen, 1926-1997 (Criterion collection, 2012)
This first work of The Qatsi Trilogy wordlessly surveys the rapidly changing environments of the Northern hemisphere, in an astonishing collage created by the director, cinematographer Ron Fricke, and composer Philip Glass. It shuttles viewers from one jaw-dropping vision to the next, moving from images of untouched nature to others depicting human beings, increasing dependence on technology.